Indonesian Teachers’ Perspectives on Gender Representation in EFL Textbook Visual Images for Elementary Schools - Rusmawaty, Desy; Hermagustiana, Istanti; Majewska, Marysia; Ahada, Ichi; Sucahyo, Didik (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Background: The use of gendered visual imagery in English as a Foreign Language (EFL) textbooks has raised concerns about perpetuating gender stereotypes and the potential effect on students' conceptions of gender roles. Despite the widespread use of mandated textbooks in primary classrooms in Indonesia, less is known about instructors' perceptions of gendered visual imagery. Methodology: This qualitative research employed a mixed-methods approach, incorporating quantitative and qualitative data collection and analytic methodologies. An investigation was conducted in Samarinda East Kalimantan to collect the perspectives of 41 teachers who teach English in elementary school regarding the gendered visual representations present in the mandatory EFL textbooks. Furthermore, 12 teachers were chosen to partake in exhaustive interviews to present more informed and profound perspectives. Findings: They merely focused on how to teach the materials rather than scrutinizing the gender bias represented through texts and visual images. The study revealed that a significant proportion of teachers (80%) believed that gendered visual imagery in textbooks was not impartial and could influence the gender roles of pupils. Furthermore, a significant majority (75%) said they often adjusted or avoided using these pictures in their teaching methods. The interviews highlighted the teachers' concern about the possible negative impact of these pictures on students' social relationships and self-image. However, they merely focused on how to teach the materials rather than scrutinizing the gender bias represented through texts and visual images Conclusion: The findings suggest that elementary school teachers in Indonesia know the potential negative repercussions of gendered visual images in EFL textbooks and have implemented measures to mitigate these effects. The study underscores the importance of incorporating diverse and inclusive visual materials into educational resources to promote gender equality and positive gender representations. This concept is new to them. They agree that gender equality needs to be addressed and discussed as part of the content in classroom practices to raise students’ awareness of gender bias. Originality: Previous studies have investigated the frequency and occurrence of gender bias in textbooks, found in images and texts. However, there is a lack of investigation into teachers' awareness of gender stereotypes in textbooks. This study enhances the existing corpus of literature by examining the perspectives of teachers on the use of gendered visual images in EFL textbooks in elementary schools in Indonesia. It emphasizes the importance of teachers and policymakers advocating for more inclusive educational resources and considering the impact of visual materials on students' gender perceptions